"Bite, Bite against the Iron Cage": The Ambivalent Dreamscape of Zoos in Colonial Seoul and Taipei. Issue 2 (May 2020) - Seeley, Joseph; Skabelund, Aaron
Abstract : This article examines the zoological gardens established by Japanese imperialists in colonial Seoul (1908) and Taipei (1914). Drawing on multilingual sources, it argues that zoos explicitly exposed the unequal interethnic and interspecies hierarchies that undergirded the colonial project. The colonial zoo was an ambivalent "dreamscape": a carefully constructed landscape of iron cages and manicured pathways wherein colonizers' dreams of ordering the natural world and colonized populations existed in uneasy tension with the actual experiences of zoo visitors and encaged zoo animals. Intellectuals sometimes criticized zoo excesses or identified the bondage of caged animals with the colonized experience. Yet these zoos also enjoyed immense popularity as Japanese, Korean, and Taiwanese visitors alike participated in the physical and discursive subjugation of zoo animals. Sensitivity to these contradictions, this essay contends, is essential for understanding both the broader significance of these institutions and their contested legacies today.